The Proposed Tollgate Price Hike's Potential Impact on Inflation in Sierra Leone: A Counterfactual Estimation - Kabineh Kpukumu; Mohamed Samba Barrie (ZBW – Leibniz Information Centre for Economics, 2024)
This research investigates the potential impact of proposed tollgate price adjustments on inflation dynamics in Sierra Leone using a suite of Bayesian Vector Autoregressive (VAR) models with data from 2007M1 to 2024M1. Around 2015-2016, the government of Sierra Leone initiated a crucial road expansion project in partnership with China Railway Seventh Group Co., Ltd. (CRSG), aiming to improve transportation networks by extending the road from Wellington in Freetown to Masiaka in Port Loko District. As per the agreement, three tollgates were to be erected at strategic points along this expanded route: Hastings, Songo, and Masiaka. Despite maintaining stable tollgate prices since their inception in 2017, CSRG has indicated recently that they want to revise the tollgate prices to reflect exchange rate depreciation, thus prompting an examination of this proposed move on inflation. Projections from the model simulations indicate that if the proposed toll gate price revisions are enacted in April 2024, transport inflation would surge by 1.55% month-on-month and by 5.3% year-on-year from April to July 2024 cumulatively. In dissecting the transport sector, our analysis revealed a clear pattern: without the tollgate effect, transport inflation showed a gradual upward trajectory. However, upon modeling the potential effects of the proposed tollgate price revisions, a sharp increase in transport inflation is observed. Moreover, food inflation is projected to experience a significant year on-year rise of 7.15% cumulatively, while headline inflation is expected to increase by 4.62% over the period from April to June 2024. Furthermore, an examination of food inflation patterns revealed an interesting trend: before accounting for the toll gate effect, food inflation showed a declining trend over the observation period. However, upon factoring in the tollgate effect, while food inflation continued to decline, it did so at levels higher than would have been the case without the toll gate effect. These insights hold key policy implications, such as closely monitoring, communicating transparently, and coordinating responses to mitigate inflationary impacts and foster economic stability.
Keywords: 330; Tollgate prices; Inflation dynamics; Bayesian VAR framework; Policy implications; Sierra Leone